A Place to Meet: The Art of Making the City’s Street - Osman, Dalia Abdel Moneim (European Journal of Sustainable Development, 2018)
Street represents the main public space for people in the outdoor environment and in some cases the only outdoor space. At the same time, the presence of people in the street provides its life. The research attempts to measure successful designed streets as places, through discussing the study of all the urban qualities, physical features and the people’s reactions in the street environment. Based on a hypothesis that all of these factors may influence the way the people feel about the outdoor environment as a place for other activities. It brings into focus the importance of the street design, especially in distinctive neighborhoods as Heliopolis in Cairo. The main aim of the study is to show how the urban qualities and the physical features of the street environment have an impact on the performance of the street as a place to meet and stay. Finally, the results revealed some facts beyond the success of the design of the city’s street primarily linked to the combination of some of the urban design qualities and the related physical features, together with the presence of people in the street’s space. Keywords: Street, Urban Qualities, pedestrians